DELAY OF PRINCIPLE B EFFECT IN INDONESIAN LANGUAGE BY INDIVIDUALS WITH DOWN SYNDROME - Lenggana, Galih Depri (2015)
Motivated by the studies conducted by Chien & Wexler (1998) and Perovic (2001), the present study investigates the existence of Delay in Principle B Effect (DPBE) in individuals with Down syndrome and typically developing children. Six subjects are involved in the present study, three individuals with DS and three typically developing children. Adopting truth value judgment task from Chien & Wexler (1998), the present study is able to draw some findings. Both delay in Principle A and Principle B are not found in both participants groups. However, despite the fact that no delay is found, the participants exhibit the same pattern: scoring low in reflexive, and quantifier. Another intriguing finding found in the present study is pause. Some short pauses are exhibited by almost all participants. Keywords: Binding principles, DPBE, Down syndrome, typically developing children Chien & Wexler (1998) dan Perovic (2001) merupakan penelitian yang mendasari penilitain ini. Penilitian ini meneliti fenomena kemunculan Delay in Principle B Effect (DPBE) yang terdapat di orang yang mengidap sindrome Down dan anak-anak normal. Enam subjek penelitian dilibatkan dalam penilitian ini, tiga diantaranya pengidap sindrome Down, dan tiga subjek lainnya merupakan anak normal. Dengan mengadaptasikan truth value judgment task yang diciptakan oleh Chien & Wexler (1998), penelitian ini menghasilkan beberapa temuan. Keterlambatan di Principle A maupun B tidak ditemukan dalam penelitian ini. Namun, meskipun keterlambatan tersebut tidak ditemukan, para subjek menunjukkan pola yang sama: memiliki nilai yang rendah di dalam eksperimen refleksif, dan kuantifier. Temuan menarik lainnya dalam penelitian ini ialah jeda (pause). Beberapa jeda ditemukan di hampir semua subjek. Kata kunci: : Binding principles, DPBE, Down syndrome, typically developing children